Macrophages induce malignant traits in mammary epithelium via IKKε/TBK1 kinases and the serine biosynthesis pathway. Issue 2 (13th January 2020) - Wilcz‐Villega, Ewa; Carter, Edward; Ironside, Alastair; Xu, Ruoyan; Mataloni, Isabella; Holdsworth, Julie; Jones, William; Moreno Béjar, Rocío; Uhlik, Lukas; Bentham, Robert B; Godinho, Susana A; Dalli, Jesmond; et al.
Abstract: During obesity, macrophages infiltrate the breast tissue leading to low‐grade chronic inflammation, a factor considered responsible for the higher risk of breast cancer associated with obesity. Here, we formally demonstrate that breast epithelial cells acquire malignant properties when exposed to medium conditioned by macrophages derived from human healthy donors. These effects were mediated by the breast cancer oncogene IKKε and its downstream target—the serine biosynthesis pathway as demonstrated by genetic or pharmacological tools. Furthermore, amlexanox, an FDA‐approved drug targeting IKKε and its homologue TBK1, delayed in vivo tumour formation in a combined genetic mouse model of breast cancer and high‐fat diet‐induced obesity/inflammation. Finally, in human breast cancer tissues, we validated the link between inflammation–IKKε and alteration of cellular metabolism. Altogether, we identified a pathway connecting obesity‐driven inflammation to breast cancer and a potential therapeutic strategy to reduce the risk of breast cancer associated with obesity. Synopsis: In this article a new pathway has been identified that links macrophage‐driven inflammation and cellular metabolism to the acquisition of malignant traits in breast epithelium providing new insight into the well‐established association between breast cancer and obesity and offering a new preventive strategy. Medium conditioned by macrophages derived from healthy donors induces acquisition of malignant properties in breast epithelial cells. Inhibition of the kinase IKKε and the serine biosynthesis pathway prevents the acquisition of the malignant phenotypes induced by macrophage‐conditioned medium. Amlexanox – an FDA approved drug targeting IKKε and its homologue TBK1 – defers tumour appearance in vivo in a combined genetic mouse model of breast cancer and high fat diet‐induced obesity/inflammation. Abstract : In this article a new pathway has been identified that links macrophage‐driven inflammation and cellular metabolism to the acquisition of malignant traits in breast epithelium providing new insight into the well‐established association between breast cancer and obesity and offering a new preventive strategy.